Big Government, High Debt, and Fiscal Adjustment in Small States - Ota, Rui.; Medina Cas, Stephanie (Washington, D.C. : International Monetary Fund, 2008)
Using a new fiscal dataset for small states, this paper analyzes the link between country size, government size, debt, and economic performance. It finds that on average small states have larger governments and higher public debt. Although there are intrinsic factors that explain why governments are bigger in small states, those with smaller governments and lower public debt tend to grow faster and are less vulnerable. Large fiscal adjustments, primarily through expenditure restraint, can underpin growth, although sometimes other elements can also impact. Since better governance is associated with lower debt, fiscal adjustment should be supported by governance improvements.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet